Islam Dan Keharmonian Kaum Di Singapura - Saifuddin Amin (Pascasarjana IAIN Metro, 2018)
This Paper aims to find out on the response of Singapore as a multi-racial country and religion towards the Muslims and its role in taking care of its racial harmony in Singapore. This mix of methods of qualitative and quantitative through the approach of direct observation has found that the government of Singapore gave a good attention for Islam. This happens in such ways that the law named AMLA and muslims in Singapore take part in keeping the racial harmony in many ways such as involving in IRO organization, choosing An-Nadhah mosques as a racial harmony centre, encouraging the dialogues between religion and the muslims. Most important role in MUIS is as official instituion to have such harmony by having seminars and khutbah as well as application of downloaded information in curriculum development based on racial harmony. As the result, it is hopeful to let this be as a research for other countries that has a different system that is similar to Singapore for the sake of a better harmony.